FIRST REPORT OF ANISANDRUS MAICHE (COLEOPTERA: CURCULIONIDAE: SCOLYTINAE) INFESTING APPLE TREES - Tobin, Kelsey N.; Moore, M. Elizabeth; Lizarraga, Sandra; Petzoldt, Jane; Reese, Corey; Lovett, Brian; Rivera, Monique J. (Zootaxa, 2024)
Ambrosia beetles (Coleoptera: Curculionidae: Scolytinae) are among the most devastating pests of orchards, nurseries, and forest ecosystems. Anisandrus maiche (Kurentzov) has been regularly captured in ethanol-baited traps along woody edges of apple (Malus domestica (Suckow) Borkh.) orchards in western New York alongside a known apple pest, Xylosandrus germanus (Blandford). However, this species has yet to be a confirmed pest of apple trees. In winter 2024, we conducted a series of dissections of potted apple trees with visible ambrosia beetle attacks (i.e. entry holes, exit holes). Our examination revealed the presence of active A. maiche galleries housing mainly larvae, a few adults, and the fungal symbiont Ambrosiella cleistominuta C. Mayers & T.C. Harr This is a first report of Anisandrus maiche attacking apple trees.